Effects of Early and Delayed Antiretroviral Therapy on Plasma Anti-CD4 Autoreactive IgG and Its Association With CD4+ T-Cell Recovery in Acute HIV-Infected Individuals - Song, Aixin; Li, Zhen; Luo, Zhenwu; Lu, Xiaofan; Wang, Rui; Liu, Lifeng; Xia, Wei; Wan, Zhuang; Zhang, Tong; Su, Bin; Jiang, Wei; Wu, Hao (Frontiers in Pharmacology, 2020)
Background: Plasma levels of anti-CD4 autoantibodies are increased in chronically HIV-infected patients and inversely correlated with CD4+ T-cell recovery under viral-suppressive antiretroviral therapy (ART). However, it remains unknown the effect of early ART on plasma anti-CD4 autoantibody levels in acute HIV infection (AHI). Methods: In this cohort study, we evaluated the effect of early and delayed initiation of ART on plasma anti-CD4 autoantibody levels in AHI individuals (n = 90). Blood samples were collected from men who had sex with men (MSM) with acute infection, pre-ART, and 4, 24, 48, and 96 weeks after ART. Plasma levels of anti-CD4 immunoglobulin G (IgG) were measured by ELISA. Results: We found that plasma anti-CD4 IgG levels were significantly increased in AHI individuals compared with healthy controls (HCs) prior to ART. Notably, early ART decreased plasma anti-CD4 IgG to the levels similar to HCs starting at 24 weeks (W). However, delayed initiation of ART did not significantly reduce plasma anti-CD4 IgG levels in AHI individuals. Moreover, the peripheral CD4+ T-cell counts were inversely correlated with plasma anti-CD4 IgG levels in AHI individuals at 48 and 96W after early ART but not after delayed ART. Conclusions: Taken together, our findings demonstrate for the first time that early ART, but not delayed initiation of ART, is effective in influencing anti-CD4 autoantibody production and recovering CD4+ T-cell counts in AHI individuals.